The analysis of Burkholderia pseudomallei virulence and efficacy of potential therapeutics - Propst, Katie L., author; Schweizer, Herbert, advisor; Dow, Steven, advisor; Gentry-Weeks, Claudia, committee member; Goehring, Lutz, committee member (Colorado State University. Libraries, 2011)
Burkholderia pseudomallei is the causative agent of the disease melioidosis and is classified as a category B Select Agent. There are currently many challenges associated with both the study of this pathogen and its treatment in the clinical setting. Prior to these studies, there was no attenuated B. pseudomallei strain available that was exempt of Select Agent regulations and approved for study outside of biosafety level 3 (BSL-3) containment, and consequently basic research on this pathogen was largely hindered. The first purpose of these studies was to extensively characterize the attenuation of two B. pseudomallei mutant strains using melioidosis animal models. The two mutants constructed were Bp82 and Bp190, Δ purM derivatives deficient in adenine and thiamine biosynthesis. These mutants were found to be fully attenuated in immune competent and immune deficient mouse and hamster melioidosis models. Bp82 is currently exempt of all Select Agent regulations and can be safely handled in the BSL-2 setting, greatly accelerating research on this priority pathogen. Since basic research on B. pseudomallei was not common in the Western world until its Select Agent classification, much is still unknown regarding the bacterial factors contributing to its virulence. A second purpose of this research was to determine whether resistance-nodulation-cell division (RND) efflux systems and iron acquisition siderophores impact the virulence of B. pseudomallei in a pneumonic murine melioidosis model. This was examined using a clinical isolate naturally devoid of a characterized efflux system and the gene cluster for malleobactin siderophore synthesis, and by the construction of isogenetic mutants. The two characterized B. pseudomallei efflux pumps, AmrAB-OprA and BpeAB-OprB, were both found to be completely dispensable during in vivo murine infection. The removal of one or both of these systems did not reduce lethality of the mutant strains. Unlike that observed with similar bacterial pathogens, the lethality of B. pseudomallei was also not reduced upon the removal of either the malleobactin or pyochelin siderophores. This finding indicates B. pseudomallei is likely capable of utilizing alternative systems for iron acquisition within the host. In addition to the challenges associated with the study of this pathogen, there are also many clinical challenges associated with melioidosis, providing a basis for the final two purposes of this research. One particular challenge is the high frequency of patient relapse, even after appropriate prolonged antibiotic therapy. A third purpose of this research was to determine whether traditional antibiotic therapy could be augmented by the co-administration of immunotherapy. Cationic liposome-DNA complexes (CLDC), which are potent activators of the innate immune system, were found to synergistically reduce intracellular B. pseudomallei concentrations in macrophages in vitro when combined with the antibiotic ceftazidime. In addition, this combination therapy also significantly increased mouse survival during both acute and chronic melioidosis. A similar enhancement to ceftazidime therapy was observed with recombinant IFN-γ, illustrating the potential of immunotherapy to improve clinical outcome and decrease patient relapse. The lack of an effective approved vaccine for human use is another substantial clinical challenge associated with melioidosis and its prevention. The final purpose of these studies was to develop an effective mucosal vaccine, offering both short-term protection from acute pneumonic disease and long-term protection from disseminated chronic melioidosis. CLDC was identified as a highly effective mucosal adjuvant within complexed to heat-killed B. pseudomallei, and this adjuvant offered moderate protection from acute disease when combined with Burkholderia protein subunits. The longest-term protection from lethal challenge in our murine model, lasting beyond 100 days, was elicited by the fully attenuated live Bp82 strain. Since this strain is both fully attenuated and exempt of Select Agent regulations, it has great potential clinically for high-risk persons as an effective live vaccine strain.
Keywords: Burkholderia; ceftazidime; CLDC; purM; vaccine; virulence